Evaluation of practice-oriented nonlinear analysis methods for seismic performance assessment - Önem, Göktürk. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2008., 2008)
In the last decade, nonlinear static analyses based on pushover analysis have been developed as a simplified nonlinear analysis tool within the context of performance based design approach (ATC 40 and FEMA 356). Since nonlinear static analyses provide designers a practical analysis approach in estimating inelastic seismic demands, these methods have been widely used in engineering practice. On the other hand, recent research have clearly shown that simplified nonlinear static analyses, which consider single mode behavior of the structures, have serious limitations for high-rise buildings or buildings irregular in plan, where higher modes effects become important. In order to overcome these limitations and to enhance the feasibility of the pushover analysis in practice, a number of multi-mode pushover analysis methods have been developed. It should be noted that pushover analysis has not been provided with a firm theoretical basis and those methods are therefore based on various assumptions. In this study, development and codification of nonlinear static analysis as a tool for performance based assessment have been summarized. Piecewise linear representation of single-mode pushover analysis, which provides a non-iterative pushover analysis technique with an adaptive load or displacement pattern, has been presented in detail. A number of multi-mode pushover analysis methods have been investigated in detail and classified with respect to their assumptions. The emphasis of this study is to evaluate the validity of those assumptions and their limitations in terms of practical applicability. In addition, a parametric study is carried out in order to evaluate and understand the limitations of single-mode and multi-mode pushover analysis methods based on various assumptions. It has been observed that some multi-mode pushover analysis methods deal with estimating only structural capacity, resulting in a conventional pushover curve where higher modes effects are somehow considered. Thus these multi-mode pushover analysis methods can be regarded only as capacity estimation tools. However, the main objective of the nonlinear static analysis should be the estimation of the seismic demands under a given earthquake ground motion. It is interesting to observe that the number of multi-mode pushover analysis methods achieving this objective is very limited. Determination of relative modal contributions at each pushover step with an appropriate modal scaling procedure is a critical point in a multi-mode pushover analysis As a result of the investigation of multi-mode pushover analysis methods, it has been observed that there are mainly two types of modal scaling procedures generally adopted: (a) scaling based on instantaneous inelastic spectral displacements, (b) scaling based on instantaneous elastic spectral displacements or pseudo-accelerations. It has been identified that multi-mode pushover methods adopting modal scaling procedure based on instantaneous elastic spectral quantities would not work when P-delta effects are considered. The effectiveness of multi-mode pushover analyses has been tested for reinforced concrete frame and dual systems by comparing the results obtained from inelastic time history analysis (ITHA). Analysis results indicated that multi-mode pushover analyses, which combine multi-mode effects at each pushover step, provides relatively good estimates of inter-story drift and plastic rotation demands in the lower and middle stories of taller frames. At the upper story levels, where higher mode effects are significant, Incremental Response Spectrum Analysis (IRSA) developed by Aydınoglu (2003) and Modal Pushover Analysis (MPA) developed by Chopra and Goel (2001) give more accurate results as compared to the other methods. It has been observed that when P-delta effects are included in the analyses, the discrepancy between the results obtained from ITHA and all pushover analyses tends to increase as compared to the case without P-delta effects. For dual systems, multi-mode pushover analyses, which combine multi-mode effects at each pushover step, predicts reasonably well the changing height-wise variation of plastic rotation demands in the beams with building height, particularly for dual systems with smaller wall shear ratio. IRSA significantly predicts much more accurate plastic rotation estimates with respect to all other multi-mode pushover methods. Single-run multi-mode pushover analysis methods with single-load or single-displacement patterns based on combined multi-mode loading significantly underestimate shear force demands in the shear wall elements. Additionally, it has been observed that multi-mode pushover analysis methods provide much more accurate estimate of plastic hinge rotations and their locations at the base of the shear walls as compared to FEMA 356 lateral load distributions. Single-mode adaptive pushover analysis can predict plastic rotation demands accurately at the base of the shear walls in spite of the fact that only single mode was considered, whereas invariant single-mode pushover analysis cannot predict. This shows that adaptive pushover analysis provides a more reliable analysis technique, which is able to capture changing dynamic characteristics of dual systems and eventually plastic rotation demands at the base of the shear walls.
Keywords: Earthquake resistant design.